Evaluation of Energy Utilisation Efficiencies of Digestible Macronutrients in Juvenile Malabar Snapper (Lutjanus malabaricus) Reveals High Protein Requirement for Optimal Growth Using Both Factorial and Multifactorial Approaches - Si Yan Ngoh; Xueyan Shen; Leo Nankervis; Katheline Hua (Aquaculture Nutrition)
Malabar snapper (Lutjanus malabaricus) is an economically important marine fish throughout the Indo-Pacific, with an emerging aquaculture industry. Although generic marine feeds are available for production, these are not optimised for this species. Understanding energy utilisation and balance can provide insight into suitable macronutrient profiles for new species to provide a baseline for future development. This study, therefore, evaluated the effect of dietary macronutrient composition (i.e., protein, fat, and carbohydrate) on the utilisation efficiencies of digestible energy (DE) in juvenile Malabar snapper using two isonitrogenous diets (high fat: HF and low fat: LF) with contrasting fat and carbohydrate content. Each diet was fed at four feeding levels (100%, 75%, 50%, and 25% apparent satiation) for 56 days, creating a 2 by 4 factorial design. The maintenance energy requirement of Malabar snapper was estimated to be 76.7 kJ kg−0.8 day−1, while the utilisation efficiencies of digestible protein (DP) and fat were 73.6% and 68.3%, respectively. Fish fed with LF, which has lower dietary fat and higher dietary carbohydrate levels, had significantly reduced energy utilisation efficiency for growth and significantly higher partial energy utilisation efficiency of digestible fat (DF) (p <0.05). Since body moisture is usually proportional to body fat content in fish, this implies that the energy from carbohydrates preferentially enters lipogenesis rather than being available for somatic growth, and adiposity does not directly result in weight gain. Malabar snapper utilises DF in preference to protein for metabolism, demonstrating a protein-sparing effect from lipids at DE intake levels below the maintenance requirement. Conversely, given the higher efficiency of fat retention than protein retention, protein is likely used before fat when energy intake is above maintenance. These findings suggest that Malabar snapper requires high levels of DP in its diet to support growth and that energy from dietary carbohydrates is diverted towards adiposity, consequently reducing growth.